Blended Learning Integration in Physics: Advancing Critical Thinking Skills on Optical Instrument Concepts - Aini, Yesma; Zakiah, Wafiqoh (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to determine the effect of the blended learning model on students' critical thinking skills on the concept of optical instruments. Methodology: The research sample was obtained through purposive sampling, consisting of class XI IPA 1 (experimental) and class XI IPA 2 (control), with 29 students in each class, for a total of 58 students. This study employed a quasi-experimental method with a nonequivalent control group design. The instrument was an essay test consisting of 10 items based on Robert H. Ennis’s critical thinking indicators. Data were analyzed using parametric tests (t-test) with the assistance of the SPSS program. Main Findings: The paired samples t-test at α = 0.05 yielded a Sig. (2-tailed) value of 0.001, indicating that H0 was rejected and H1 accepted. This confirms a significant difference in students’ critical thinking skills between the experimental and control classes. The blended learning model enhanced students’ performance, with the experimental class achieving a higher N-gain (0.63, medium) than the control class (0.33, medium). Nonetheless, improvement remained modest in the indicator of answering clarification questions (N-gain = 0.43). Novelty/Originality of this study: This study highlights the originality of integrating a blended learning model supported by Google Classroom to improve students’ critical thinking skills in physics, specifically on optical instruments. The novelty lies in combining digital learning platforms with classroom instruction, demonstrating not only improved learning outcomes but also fostering students’ independence and active engagement, thus extending existing knowledge in blended physics education.